2019
DOI: 10.1093/annonc/mdz047
|View full text |Cite
|
Sign up to set email alerts
|

The immune profile of small HER2-positive breast cancers: a secondary analysis from the APT trial

Abstract: Background: Previous data suggest that the immune microenvironment plays a critical role in human epidermal growth factor receptor 2 (HER2) -positive breast cancer; however, there is little known about the immune profiles of small HER2-positive tumors. In this study, we aimed to characterize the immune microenvironment of small HER2-positive breast cancers included in the Adjuvant paclitaxel and trastuzumab for node-negative, HER2-positive breast cancer (APT) trial and to correlate the immune markers with path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Within HER2-positive BC, the level of TILs varies according to the molecular intrinsic subtype, being higher in basal-like and HER2-enriched tumors [86].…”
Section: Tumor Immune Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Within HER2-positive BC, the level of TILs varies according to the molecular intrinsic subtype, being higher in basal-like and HER2-enriched tumors [86].…”
Section: Tumor Immune Microenvironmentmentioning
confidence: 99%
“…In early HER2-positive BC, higher TILs have been associated with both increased likelihood of pCR after neoadjuvant therapy [84] and with improved prognosis [87]. TILs have also been shown a significant positive correlation with PD-L1 expression in both early and metastatic HER2-positive BC samples [86,88].…”
Section: Tumor Immune Microenvironmentmentioning
confidence: 99%
“…3,6,[10][11][12][13][14][15][16][17] At a DNA level, PIK3CA mutations have also been associated with lower treatment response. 18,19 Apart from intrinsic tumor characteristics, different immune system features have been correlated with a higher pCR rate in HER2-positive breast cancer, including the presence of tumor-infiltrating lymphocytes (TILs), 14,[20][21][22][23][24] programmed death ligand-1 protein expression, 23 T-cell receptor diversity metrics, 25 and immune gene-expression signatures. 3,12,26 TILs in the NeoALTTO trial 22 showed a significant association with survival.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that in early stage, around 50 % of cHER2+ BC present with ≥10 % TILs, around 20 % shows ≥20 % and about 10 % ≥ 40 % TILs ( Fig. 4 ) [ [78] , [79] , [80] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%